Implementasi Preorder Traversal Dalam Rekomendasi Produk Toko Bangunan Dunia Baru - Elizabeth, Triana; Tinaliah, Tinaliah (Universitas Multi Data Palembang, 2025)
Toko Bangunan Dunia Baru Palembang has implemented a sales application system since 2018 to improve operational efficiency. Although a discount feature has already been included, the application still lacks an automatic product recommendation feature. In fact, such a feature is essential for boosting sales by suggesting related products that are often purchased together. This research aims to design and develop a product recommendation application using a binary tree data structure with the preorder traversal algorithm. This method enables the system to provide product suggestions based on the hierarchical relationship between main products and supporting products. The research was conducted through literature review, direct observation, collecting sales data, grouping data based on product categories and co-purchase frequency, designing the tree data structure, implementing the algorithm, and testing the application. The test results show that the feature is easy to use for employees and can assist them in providing quick and logical product recommendations. However, some issues were identified, such as the font size being difficult to read and the lack of product details—such as brand and stock availability—on the same display.